1992
DOI: 10.1109/27.199499
|View full text |Cite
|
Sign up to set email alerts
|

Double-layer-relevant laboratory results

Abstract: Also, magnetic sheaths have been experimentally studied and compared with theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Such phenomena have been observed in laboratory generated discharges at different gas pressures, including atmospheric pressure [2], [3]. On the other hand, multilayer structures have been observed in both space plasmas and low-pressure glow discharges, usually in the form of a double-layer or multiple double-layers [4]. They are also known as striation [1].…”
Section: Multilayer Plasma Patterns In Atmosphericmentioning
confidence: 98%
“…Such phenomena have been observed in laboratory generated discharges at different gas pressures, including atmospheric pressure [2], [3]. On the other hand, multilayer structures have been observed in both space plasmas and low-pressure glow discharges, usually in the form of a double-layer or multiple double-layers [4]. They are also known as striation [1].…”
Section: Multilayer Plasma Patterns In Atmosphericmentioning
confidence: 98%
“…Observations in the ionosphere and magnetosphere have shown that plasma is not only flowing due to the expanding magnetic field lines; double layers (DLs) set up electric fields parallel to the magnetic field in the polar cavity and accelerate the plasma ions and electrons to supersonic speeds and beams [3][4][5]. Over the years, DLs have been studied in great detail both theoretically and experimentally, as described in several reviews [6][7][8] and more specific works [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…1 highlights a distinct nature of self-organization. The multilayer plasma pattern is sometimes known as striation structure [5], [6]. In our experiments, the four striated atmospheric glow discharges were very stable and appeared stationary even though their excitation was at a higher frequency.…”
mentioning
confidence: 66%
“…Broadly there are two different groups of self-organized patterns, namely: 1) self-organization of multiple plasmas simultaneously sustained between two parallel electrodes [3], [4], and 2) self-organized multilayer patterns developed along the length of a single plasma column [5], [6]. In this paper, we report observation of multilayer structures in each of several self-organized atmospheric pressure glow discharges (APGD) sustained simultaneously with a single power source.…”
mentioning
confidence: 97%